2021
DOI: 10.1186/s12985-021-01716-8
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C virus DNA vaccines: a systematic review

Abstract: Background Vaccination against HCV is an effective measure in reduction of virus-related public health burden and mortality. However, no prophylactic vaccine is available as of yet. DNA-based immunization is a promising modality to generate cellular and humoral immune responses. The objective of this study is to provide a systematic review of HCV DNA vaccines and investigate and discuss the strategies employed to optimize their efficacies. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 89 publications
(87 reference statements)
0
5
0
Order By: Relevance
“…The triple doses of peptide vaccine induced a higher level of IFN-γ/IL-4 ratio as compared to other tested combinations [47]. Another study has indicated that the vaccination of BALB/c mice with a dose of 800 ng to 16 µg of multiple antigenic peptides made by combining conserved epitopes of HCV E1, E2, NS4B, NS5A, and NS5B has produced elevated immunogenic responses and caused an induction of IFN-γ-producing CD4+/CD8+ T-lymphocytes in the immunized mice [15,48].…”
Section: Use Of Multi-epitopesmentioning
confidence: 99%
See 2 more Smart Citations
“…The triple doses of peptide vaccine induced a higher level of IFN-γ/IL-4 ratio as compared to other tested combinations [47]. Another study has indicated that the vaccination of BALB/c mice with a dose of 800 ng to 16 µg of multiple antigenic peptides made by combining conserved epitopes of HCV E1, E2, NS4B, NS5A, and NS5B has produced elevated immunogenic responses and caused an induction of IFN-γ-producing CD4+/CD8+ T-lymphocytes in the immunized mice [15,48].…”
Section: Use Of Multi-epitopesmentioning
confidence: 99%
“…The continuous advancement of global research has provided significant and valuable insights into the structural and non-structural proteins of HCV to identify the main targets and epitopes for effective HCV vaccine design and development. While the Core, E1, and E2 proteins have been predominantly utilized as vaccine targets compared to the nonstructural proteins, ongoing efforts aim to explore the full potential of these proteins in HCV vaccine design [12][13][14][15][16][17][18][19][20][21][22][23][24][25]. The ORF encodes a single polyprotein of approximately 3030 amino acids, which is processed co-and post-translationally by various cellular and viral proteases into three structural proteins (Core, E1, and E2) at the N-terminus and seven non-structural proteins (P7, NS2, NS3, NS4A, NS4B, NS5A, and NS5B) at the C-terminus.…”
Section: Structural and Non-structural Protein Antigens As Targets Fo...mentioning
confidence: 99%
See 1 more Smart Citation
“…Plasmid DNA encoding antigenic HCV protein(s) or epitope(s) can induce both humoral and cellular immune responses in vivo [ 132 ]. DNA vaccines include the nucleotides encoding structural proteins or nonstructural proteins, such as NS3, NS4, NS5, core, and the envelope proteins E1/E2 [ 133 ]. CIGB-230, containing a mixture of core/E1/E2-expressing plasmids, was the first therapeutic DNA vaccine for HCV evaluated in clinical trials [ 134 , 135 ].…”
Section: Therapeutic Vaccines Against Infectious Diseasesmentioning
confidence: 99%
“…Hepatitis C virus (HCV) is a serious international health threat that persistently infects around 170 million individuals worldwide (∼2% of the world's population). It is estimated that there are three to four million people are infected with HCV annually; the majority of HCV-infected cases remain undetected as chronic HCV carriers because HCV infection barely presented with clinical manifestation earlier than the onset of advanced liver disease stage [ 1 ]. Chronic infection with HCV is associated with end-stage liver disease e.g.…”
mentioning
confidence: 99%